Hubungan Antara Mendengarkan Musik dan Perubahan Mood - Dian Tri Andini; Fikri Khusaini; Safa Puja Arsila; Sri Mulyeni (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
The study aims to measure how human emotional states are affected by music, both in increasing happiness and helping individuals manage sadness, musical characteristics such as tempo, tonality, and lyrics play an important role in shaping listeners' affective responses, where upbeat music with fast tempo and major tonality tends to promote positive moods, while melancholy music with slow tempo and minor tonality is more likely to evoke mood reflective or sad. This study used a pseudo-experimental method with a pre-test and post-test design on a group of psychology students of the National University of PASIM, with two songs as a stimulus: "I Love U Bibeh" by The Changcuters and "Jiwa Yang Bersad" by Ghea Indrawati. The measurement instrument was a simple question about the mood of the respondents with a choice of sad or happy. The results showed that the song I Love U Bibeh increased the number of students who reported feeling happy from 30% to 76.7%, while the song Jiwa yang Bersad increased the number of students who reported feelings of sadness from 40% to 63.3%, although some respondents reported catharsis in the form of emotional relief. The discussion emphasized that music has a dual function, namely as a stimulus that is able to change mood as well as a means of regulating emotions through catharsis, with effectiveness that is also influenced by cultural closeness and individual music preferences. The conclusion of this study is that music can be seen as a relevant scientific instrument in supporting students' mental health, strengthening cultural identity, and improving the quality of life, so that the choice of music can be adjusted to emotional needs, both to increase happiness and to help accept and manage sadness.